Psychological distress among patients awaiting histopathologic results after prostate biopsy: An unaddressed concern. Issue 3 (August 2022) - Sarchi, Luca; Eissa, Ahmed; Puliatti, Stefano; Amato, Marco; Assumma, Simone; Calcagnile, Tommaso; Ticonosco, Marco; Iseppi, Andrea; Toso, Stefano; Sighinolfi, Maria Chiara; Bianchi, Giampaolo; Micali, Salvatore; et al.
Background: Prostate cancer is the most commonly diagnosed neoplasm in men. From the introduction of PSA testing, an increasing number of men undergoes prostate biopsy (PBX). While the physical side effects of PBx have been well investigated, its psychological impact has been under-evaluated. Aim: The aim of our study is to investigate the presence of psychological distress (anxiety and depression) in patients waiting for histopathological results after prostate biopsy (PBx). Methods: From February to April 2019, 51 consecutive patients undergoing prostate biopsies at our institution were included. Age, PSA, DRE, familiarity for prostate cancer, number of previous biopsies, type of anesthesia, number of cores were recorded. All patients filled the Hospital Anxiety and Depression Scale (HADS), a psychometric Likert-scale questionnaire, before receiving the histopathological results of their PBx. Results: The prevalence of psychological distress among patients awaiting histopathologic results is 41% (21/51 patients), with anxiety being the main component of their distress. On multivariate analysis, PSA, family history, and repeat biopsy were significantly associated with anxiety and depression. Conclusion: Patients undergoing PBx experience a burden of psychological distress waiting for histopathologic results, especially anxiety. Appropriate counseling should be offered to patients at high risk of developing psychological distress after PBx. Future goals would include technological improvements to shorten the time between biopsy and definitive results.